IMPROVING STUDENTS’ ENGLISH VOCABULARY MASTERY BY USING WORDWALL MEDIA IN GRADE 8 MTs HUBBUL WATHAN TABUYUNG - Yusmiarni; Eliza, Eliza; Merry Prima Dewi; Widya Syafitri (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
Some of the problems in students' mastery of vocabulary are very diverse, ranging from errors in spelling, pronunciation, and choosing the right words in writing and speaking. This research aims to analyze the increase in vocabulary mastery of students in class VIII at MTs HUBBUL WATHAN TABUYUNG, through the use of wordwall learning media. This research is classroom action research. The subjects of this research were 24 class VIII students, the data collection technique was in the form of tests. The average student score before using wordwall media was 73.00. The results of data analysis show that the average score of students' vocabulary tests in cycle I was 98.75 and the average score of students' vocabulary tests in cycle II was 99.5. Cycle II experienced an increase of 26.5 from the average student score before using wordwall media. So it can be concluded that student learning outcomes in vocabulary mastery through the use of wordwall media in class VIII MTs HUBBUL WATHAN TABUYUNG students have increased. This research hopes that English teachers will use wordwall learning media because it can improve students' vocabulary mastery.